A quantitative reward prediction error signal in ventral pallidum - Ottenheimer, David J. (Nat Neurosci, 2020)
The nervous system is hypothesized to compute reward prediction errors (RPEs) to promote adaptive behavior. Correlates of RPEs have been observed in the midbrain dopamine system, but the extent to which RPE signals exist in other regions implicated in reward processing is less well understood. Here, we quantified outcome history-based RPE signals in the ventral pallidum (VP), a basal ganglia nucleus functionally linked to reward-seeking behavior. We trained rats to respond to reward-predicting cues and fit computational models to the firing rates of individual neurons at the time of reward delivery. We found that a subset of VP neurons encoded RPEs and did so more robustly than nucleus accumbens, an input to VP. VP RPEs predicted changes in task engagement, and optogenetic manipulation of VP during reward delivery bidirectionally altered rats’ subsequent reward-seeking behavior. Our data suggest a pivotal role for VP in computing teaching signals that influence adaptive reward seeking.